2015
DOI: 10.2220/biomedres.36.187
|View full text |Cite
|
Sign up to set email alerts
|

<b>Increased expression of 5-HT</b><b><sub>2A</sub></b><b> and 5-HT</b><b><sub>2B</sub></b><b> receptors in detrusor muscle after partial bladder outlet obstruction in </b><b>rats </b>

Abstract: Serotonin (5-hydroxytryptamine; 5-HT)-induced bladder contraction is enhanced after partial bladder outlet obstruction (pBOO) in rats. We investigated time-dependent changes in bladder contraction and expression of 5-HT 2A and 5-HT 2B receptor mRNA in bladder tissue to elucidate the mechanism of this enhancement. On day 3 and 7 after pBOO, contractile responses of isolated rat bladder strips to 5-HT were increased compared with that in sham-operated rats; on day 14, the response had decreased to the same level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
0
6
0
1
Order By: Relevance
“…A large number of studies focused on the compensated phase. The typical histological appearance of the wall of the pBOO bladder is bladder hypertrophy by wall thickness and a significant increase in bladder weight, which is similarly observed in patients with BPH . Electron microscopic studies have shown that muscle hypertrophy and hyperplasia increased collagen deposition and a loss of parasympathetic nerve terminals, which could result from unstable electrical status and might have spread disordered patterns of current .…”
Section: Morphologymentioning
confidence: 84%
“…A large number of studies focused on the compensated phase. The typical histological appearance of the wall of the pBOO bladder is bladder hypertrophy by wall thickness and a significant increase in bladder weight, which is similarly observed in patients with BPH . Electron microscopic studies have shown that muscle hypertrophy and hyperplasia increased collagen deposition and a loss of parasympathetic nerve terminals, which could result from unstable electrical status and might have spread disordered patterns of current .…”
Section: Morphologymentioning
confidence: 84%
“…Interestingly, we also noted that DOI improved the storage dysfunction, as shown by a reduction in NVCs in SCI. Previous studies have reported that 5‐HT 2A and 5‐HT 2C exist in the bladder of both humans and rats . Moreover, it has been reported that the 5‐HT2 receptor plays a major role in the effects of serotonin on the responses of the rat bladder contractions ; thus, we speculate that the effect of DOI on NVCs is exerted via its direct effect on the bladder, strengthening the contractile force of the bladder to promote effective voiding.…”
Section: Discussionmentioning
confidence: 70%
“…This phenomenon might be related to the mechanism(s) whereby this compound relieves storage symptoms in BPH patients. A previous investigation reported that the expression of 5‐HT2A and 5‐HT2B receptors in the bladder is upregulated in the very early phase of pBOO in the rat model 24 . Khan et al.…”
Section: Discussionmentioning
confidence: 97%
“…A previous investigation reported that the expression of 5-HT2A and 5-HT2B receptors in the bladder is upregulated in the very early phase of pBOO in the rat model. 24 Khan et al used autoradiography to show a significant time-dependent upregulation of neuronal 5-HT binding sites in the detrusor muscle of rabbits subjected to pBOO. 25 Specifically, at 6 weeks after surgical induction of pBOO, samples of detrusor muscle showed an increase in the number of 5-HT binding sites, a change not seen in the early phase of pBOO, indicating the existence of a critical window for the effects of pBOO.…”
Section: Discussionmentioning
confidence: 99%